2022
DOI: 10.1002/1348-9585.12356
|View full text |Cite
|
Sign up to set email alerts
|

The effect of job strain and worksite social support on reported adverse reactions of COVID-19 vaccine: A prospective study of employees in Japan

Abstract: Objectives This prospective study aimed to examine the association of psychosocial working conditions with adverse reactions after receiving COVID‐19 vaccination in a sample of employees in Japan. Methods The data were retrieved from an online panel of full‐time employees (E‐COCO‐J). The analysis included participants who were employed and were not vaccinated at baseline (June 2021) but received vaccination at a 4‐month follow‐up (October 2021). An 11‐item scale measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A study also reported that COVID-19 vaccine associated anxiety increased reported adverse reactions to vaccination in patients with chronic liver disease [55]. Similarly, a Japanese study suggested that psychological distress was positively associated with adverse reactions after COVID-19 vaccination [56]. Vaccine enters the body and immediately activate the immune system, and inflammatory cytokines are released from macrophages due to early innate immune response [28].…”
Section: Discussionmentioning
confidence: 99%
“…A study also reported that COVID-19 vaccine associated anxiety increased reported adverse reactions to vaccination in patients with chronic liver disease [55]. Similarly, a Japanese study suggested that psychological distress was positively associated with adverse reactions after COVID-19 vaccination [56]. Vaccine enters the body and immediately activate the immune system, and inflammatory cytokines are released from macrophages due to early innate immune response [28].…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is that the burden of commuting and working full-time can be reduced. Although scholars pointed out many advantages of teleworking during the COVID-19 pandemic 31) , certain disadvantages were also observed, such as increased stress due to mismatch between telecommuting preference and frequency 29) , reduced social support 32) , and increased alcohol consumption 33) . Therefore, taking advantage of the benefits of teleworking is necessary to support the balance between treatment and work, while also identifying any difficulties with new work arrangements, gaining opportunities for communication, and ensuring that regular lifestyle habits are not hindered.…”
Section: Discussionmentioning
confidence: 99%